Authoritative parenting style and aggression in adolescents: Mediating role of machiavellianism - SAMIUL BISWAS; Dr. Anshu Narad (Journal of Interdisciplinary Studies in Education, 2026)
Authoritative parenting promotes warmth and control, aggression reflects hostile behaviour, while Machiavellianism involves manipulative interpersonal strategies. This study investigated how Authoritative parenting style relates to aggression, focusing on how Machiavellianism—a trait from the Dark Triad Personality framework—acts as a mediator. 445 secondary school students from West Bengal, India, took part in the research. The study used standardized tools: Parental Authority Questionnaire (Buri, 1991), Short Form Aggression Questionnaire (Bryant & Smith, 2001), and Short Dark Triad (Jones & Paulhus, 2013). The findings showed notable gender differences in both Aggression and Machiavellianism. Correlation analysis revealed a positive link between Aggression and Machiavellianism, and a negative correlation with both fathers’ and mothers’ Authoritative parenting style.